Towards Querying Implicit Knowledge in XML Documents - Lima, Diego; Delgado, Carla; Murta, Leonardo; Braganholo, Vanessa (Journal of Information and Data Management, 2012)
The expressive growth in the volume of data stored as XML stimulates the improvement of methods for obtaining novel ways to explore this information. Methods for providing elaborated answers to increasingly more complex queries were recently investigated, but existing approaches mainly analyze information that is explicitly defined in the XML document. This work presents an approach that is capable of processing implicit knowledge through inference, guided by user defined rules. This can cause a significant increase in the query possibilities, allowing easy access to new information, serendipitous results and providing for more elaborate queries.